Avaliação institucional da educação superior: normas e saberes na constituição da atividade do coordenador da CPA na UEG - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This research is located in the line of research Education, School and Technologies, whose thematic axis applies to the study of Educational Public Policies, Higher Education, Education and Work. The general objective of this study is to understand the activity of the coordinator within the scope of the Evaluation Committee (CPA), considering the norms and knowledge as constitutive elements in the work of the internal evaluator. It is a qualitative approach with emphasis on the work perspective of the internal evaluation coordinator of a multicampi university in the state of Goiás. The question that arises as a central problem is: to what extent do norms and knowledge constitute the work of the CPA coordinator? To deepen the issue, a literature review was carried out that has the activity and internal evaluation as the focus of study. The methodological path includes document analysis, based on the Institutional Assessment Program of Brazilian Universities (PAIUB), the National Course Examination (ENC) and the National Higher Education Assessment System (SINAES). In the literature review, the theoretical framework that supports this research includes authors from the field of Evaluation (AFONSO, A. J.; FREITAS, L. C.; LEITE, D.; RISTOFF, D; SCRIVEN, M; SOBRINHO J. D); interpreters and precursors in the field of Ergology (ALVES, W. F.; CUNHA, D. M.; DURRIVE, L.; SCHWARTZ, Y.). From the bibliographical readings and the used matrices, the following categories of analysis emerged: activity; norms and knowledge. The field research had as locus of study the State University of Goiás – UEG and included as participants in this study: (i) CPA Evaluation Managers; (ii) coordinating professors of the Evaluation Committee (CPA); (iii) advisors to the CPA's Evaluation Management. The empirical research was developed through an open questionnaire, using Google Forms. The questionnaire was structured based on three blocks of questions: (1) What do the norms teach in carrying out the task? (2) What are the lags in carrying out the work of the CPA? (3) Which knowledge arises from the experiences in carrying out the task? The following research findings are highlighted: Evaluation policies delineate the operational basis of the work of the internal evaluation committee and have a significant influence on task orientation in terms of the aluator's identity, mission, responsibilities and ethical standards for the coordinator of the CPA. In short, fidelity to the rules of the trade reveals the order of safety and stability at work. Regarding the activity of those who coordinate the CPA, some conflicts are pointed out in relation to technical aspects and the external and internal policy of the UEG to broader and more subjective issues involving the effectiveness, safety, credibility of the institutional assessment and the demand for results of the CPA coordinators. In the relationship between training, qualification and the work of the CPA, it was observed that the prominent positions in the UEG Evaluation Committee, such as in the positions called President of the CPA or Evaluation Management (GerAI), have a strong relationship with academic training in the field of Institutional Evaluation, as well as with the time of his professional trajectory at UEG, especially in activities related to course coordination and the Rectory. On the other hand, there is no relationship between specific training in AAI in the assignment/distribution of CPA representatives/coordinators on their respective campuses. With regard to learning and the knowledge attributed to carrying out the task, it was observed that they returned to pre-established assumptions in the scientific, technical and political knowledge of the evaluation.
Institutional evaluation of higher education: norms and knowledge in the constitution of the activity of the CPA coordinator at UEG.
Keywords: Educação Superior - UEG; Comissão Própria de Avaliação (CPA) - UEG; Ergologia - UEG; Avaliação Institucional - UEG; Autoavaliação; College education - UEG; Own Evaluation Committee (CPA) - UEG; Ergology - UEG; Institutional Assessment - UEG; Self- Assessment; CIENCIAS HUMANAS::EDUCACAO